Pemikiran Omar Mohammad Al-Syaibany Tentang Pendidikan Dan Relevansinya Dengan Pendidikan Islam Kontemporer - Salsabila, Yulia Rakhma; Yunita, Yunita; Siregar, Maragustam (PT. Student Rihlah Indonesia, 2025)
The purpose of this research is to describe Omar Mohammad Al-Toumy Al-Syaibany's thoughts on Islamic education and analyze their relevance in the contemporary era. This research is a library research with the primary source being the book entitled “Falsafah Pendidikan Islam” (Philosophy of Islamic Education) by Omar Mohammad Al-Toumy Al-Syaibany. The secondary sources used are journals, books, articles, and other sources relevant to this research. The results of this study indicate that Omar Mohammad Al Syaibany is a Muslim educational figure who discusses the philosophy of Islamic education. The rapid development of the times requires Islamic education to adapt to the demands of the times in order to be in line with the needs of society. Omar Mohammad Al-Toumy Al-Syaibany's thoughts on Islamic education include: the concept of objectives in Islamic education, the Islamic education curriculum, and teaching methods in Islamic education. These educational ideas are still relevant to contemporary Islamic education. This research implies the need for Islamic education policies that integrate knowledge and morals and emphasize holistic character building.